2022
DOI: 10.1002/hbm.25946
|View full text |Cite
|
Sign up to set email alerts
|

Brain serotonin transporter is associated with cognitive‐affective biases in healthy individuals

Abstract: Cognitive affective biases describe the tendency to process negative information or positive information over the other. These biases can be modulated by changing extracellular serotonin (5‐HT) levels in the brain, for example, by pharmacologically blocking and downregulating the 5‐HT transporter (5‐HTT), which remediates negative affective bias. This suggests that higher levels of 5‐HTT are linked to a priority of negative information over positive, but this link remains to be tested in vivo in healthy indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Data included in the current study has been utilized in previous studies 9 , 10 , 23 , 45 , 47 , some of which focused on the relation between 5-HTTLPR and/or BDNF rs6265 [ 11 C]DASB binding 23 , 45 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data included in the current study has been utilized in previous studies 9 , 10 , 23 , 45 , 47 , some of which focused on the relation between 5-HTTLPR and/or BDNF rs6265 [ 11 C]DASB binding 23 , 45 .…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has reported a link between 5-HTT levels and both healthy and pathological behavioral phenotypes. Increased 5-HTT availability (expressed in terms of binding potential, 5-HTT BP) has been linked to depressive symptoms severity in seasonal affective disorder 9 , greater negative affective bias 10 , 11 and reduced amygdala reactivity to threat in healthy individuals 12 , 13 , whereas low 5-HTT availability has been associated with childhood abuse in patients with depression vs patients who did not experience childhood abuse 14 . Notably, some studies have speculated that 5-HTT availability may be used as a marker of serotonin tone and a histochemical marker for serotonergic projections 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Neocortical (a volume-weighted average of all cortical regions) [ 11 C]-Cimbi-36 BP ND was chosen as our primary outcome region based on findings from our previous study ( Madsen et al, 2020 ), the high expression of 5-HT 2A R within neocortex ( Beliveau et al, 2017 ) and the high degree of inter-regional correlation across neocortical subregions ( Erritzoe et al, 2010 ; Spies et al, 2020 ). As secondary outcomes for post-hoc analyses, [ 11 C]-Cimbi-36 BP ND in frontolimbic regions [frontal cortex, left and right amygdala and left and right anterior cingulate cortex (ACC)] were chosen based on a previous study ( Armand et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%